Effect of sexual partnerships on Zika virus transmission in virus-endemic region, Northeast Brazil - Magalhaes, Tereza; Coelho, Flávio Codeço; Souza, Wayner V.; Viana, Isabelle F. T.; Jänisch, Thomas; Marques, Ernesto T. A.; Foy, Brian D.; Braga, Cynthia (Emerging infectious diseases, 2024)
The epidemiologic effects of Zika virus (ZIKV) sexual transmission in virus-endemic countries remain unclear. We conducted a 2-level, linear mixed-effects logistic regression analysis by using a recently acquired population-based ZIKV and chikungunya virus (CHIKV) serologic dataset obtained from persons residing in Northeast Brazil (n = 2,070 participants). We adjusted mathematical models for housing type and age of participants; the models indicated a significantly higher likelihood of ZIKV seropositivity among persons engaged in a sexual relationship within the same household (odds ratio 1.25 [95% CI 1.00–1.55]; p = 0.047), regardless of their partner’s ZIKV serostatus, and among participants with a ZIKV-seropositive sex partner within the same household (odds ratio 1.54 [95% CI 1.18–2.01]; p = 0.002). CHIKV was also modeled as a control; no sex-associated effects were observed for CHIKV serology. Inclusion of ZIKV sexual transmission in prevention and control strategies is urgently needed, particularly in ZIKV-endemic regions.